2004
DOI: 10.1016/j.jacc.2004.01.024
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian study of the sirolimus-eluting stent in the treatment of patients with long de novo lesions in small native coronary arteries (C-SIRIUS)

Abstract: Patients with long lesions in small vessels are at very high risk of restenosis. In these patients, the SES dramatically reduces the risk of restenosis at eight months, translating into an excellent clinical outcome at nine months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
254
1
24

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(308 citation statements)
references
References 19 publications
(19 reference statements)
17
254
1
24
Order By: Relevance
“…The present study showed a TLR rate of 9.3%, which can be considered low in comparison to that found for bare metal stents; this rate is in agreement with those of large studies on Taxus [11][12][13][14] and Cypher 15,16 implantation. The event-free survival curve for TLR was 88%, similar to data from the literature for the use of DES [11][12][13][14][15] .…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The present study showed a TLR rate of 9.3%, which can be considered low in comparison to that found for bare metal stents; this rate is in agreement with those of large studies on Taxus [11][12][13][14] and Cypher 15,16 implantation. The event-free survival curve for TLR was 88%, similar to data from the literature for the use of DES [11][12][13][14][15] .…”
supporting
confidence: 92%
“…The ISAR-DIABETES study 19 compared Taxus™ to Cypher™ stents and did not find significant differences in TLR rates, which were low (approximately 10%). In the subgroup analysis, the different studies on Taxus™ and Cypher™ demonstrated favorable results in diabetic patients [11][12][13][14][15][16] . According to Kereiakes and Young 20 , in this new era of treatment, the use of Taxus™ or Cypher™ DES in diabetic patients with multivessel disease proved effective in reducing angiographic restenosis and TLR rates.…”
mentioning
confidence: 96%
“…The very low 1-year rate of target lesion revascularization observed in RAVEL has been corroborated in SIRIUS (Multicenter, Randomized, Double-Blind Study of the Sirolimus-Coated BX VELOCITY Balloon Expandable Stent in the Treatment of Patients With De Novo Native Coronary Artery Lesions), E-SIRIUS, and C-SIRIUS, larger trials that enrolled subsets of patients at considerably higher risk of restenosis than the RAVEL patient population. [11][12][13] In light of the observations made during longer-term follow-up in clinical studies of several other antirestenosis agents, 16 -19 it is imperative to demonstrate the absence of both late "catch-up" restenosis and late stent thrombosis when evaluating new strategies aimed at eliminating in-stent restenosis. This is the first randomized, controlled trial of a drug-eluting stent to demonstrate sustained safety and efficacy up to 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Out of these 17 studies, three [13][14][15] were excluded because of lack of a control group and one [16] was excluded because the patient population was different from the rest of the studies. A total of 13 trials [17][18][19][20][21][22][23][24][25][26][27][28][29], with 4372 patients were included in the meta-analysis. The TAXUS-1, TAXUS-II, TAXUS-IV, RAVEL, SIRIUS, E-SIRIUS and C-CIRIUS trials were available as published reports in journals, the rest were either conference reports or abstracts.…”
Section: Resultsmentioning
confidence: 99%